Rotifers from high altitude crater-lakes at Nevado de Toluca Volcano, México. - Sarma, S. S. S.; Elías-Gutiérrez, Manuel; Serranía Soto, Carmen (HIDROBIOLÓGICA, 2016)
A survey on the high-altitude lakes El Sol and La Luna located in the crater of the volcano Nevado de Toluca, was carried out for rotifer fauna. Samples were taken with a mesh of 60 um from the littoral and limnetic zones of both lagoons in 1994. Results include 34 specific taxa representing 10 families and 16 genera. In total 11 species are new records to the fauna of México viz. Aspelta lestes, Cephalodella tenuiseta, Dicranophorus forcipatus, Lecane inopinata, Lecane scutata, Lepadella rhomboides, Notommata glyphura, Taphrocampa annulosa, Testudinella emarginula, Trichocerca bidens and Trichocerca collaris. The fauna found emphasizes the transition between neartics and neotropics of the Mexican altiplano.